The Evaluation Of Hospital Patient Safety Incident Reporting Program In Hospital - Asrofi Asrofi; Wiwik Kusumawati; Elsye Maria Rosa (Program Studi Magister Manajemen Rumah Sakit, Jenjang Pasca Sarjana (S2), Pasca Sarjana Universitas Muhammadiyah Yogyakarta, 2018)
Background: The raising number of patient safety incident is one of the major hospital problems. Reporting patient safety incident is the best method to improve the patient safety.Objective of the Research: To evaluate the realization of the patient safety incident reporting program. Methods: This research used mixed method that combined quantitative and qualitative approach. The subjects of this research were nurses, doctors and the other health officers. The samples of this research were 195 health officers by using proportionate stratified random sampling and purposive sampling technique. Analyzes test using percentage and thematic analyzes. Results: There are 194 incidents report recorded in 2017, 48 % involving the unexpected incident, 28% nearmiss, 22% not injured and 2% sentinel. Based on the patient safety culture survey, there are only 3 of 12 patients safety culture dimension that already meet the standards, there are feedback and the communication about the error (75%), learning organization and upgrading process (79%) and good teamwork in the hospital (85%). While patient safety incident reporting culture is still below the specified standard. This research olso has identified successfully the barriers of the patient safety incident report, they are lack of the knowledge, blamming and punishment culture, lack of peer support, lack of leadership support, not reported the small incident, lack of time, lack of form and incident reporting is still considered as the duty of nurses. Conclusions: The patient safety incident reporting program has worked, but it has not been agood culture. This is caused by some barriers factor.